P276 Development of patient reported experience measure (PREM) for idiopathic pulmonary fibrosis (IPF). (15th November 2016) - Russell, AM; Sonecha, S; Datta, A; Hewitt, R; Howell, I; Elliott, A; Wickremasinghe, M
Abstract : Background: Research into patient experiences of living with IPF has increased. A key challenge is how to use this data intelligently to enable commissioners and providers to improve the quality of services delivered to this group of patients. This project aims to develop an IPF-PREM informed by patients' perceptions of their healthcare experiences. The IPF-PREM is underpinned by the NHS Patient Experience Framework (NPEF); 1 National Institute for Health and Care Excellence (NICE) Quality Standards (QS15 and 79) and aligned to national initiatives integrating Patient Reported Outcome Measures (PROMs) and PREMs into NHS care. Methods: A scoping exercise was undertaken with patients diagnosed with IPF on their journey through the healthcare system covering eight areas corresponding to the NPEF. 1 Twenty patients representing all stages of the disease trajectory participated in one of three focus groups. Transcripts underwent content and thematic analysis. Patient preferences were also sought on questionnaire design. Results: A number of key themes emerged. See Table 1 . Of particular importance were issues concerning access: to specialist centres, medication and primary care services; consistency of care to prevent confusion; coordination of care especially for patients with multi-morbidities and getting the right information at the right time in the right way. Information enabling practical self-management was highly valued. Overarching was the need for continuity of care close to home. Participants valued having a nurse to co-ordinate care and to talk to at all s tages of the care pathway. The response categories patients were keen to avoid were visual images such as smiley faces. Conclusions: The IPF-PREM will provide a valuable quality indicator for IPF service delivery at all stages of the disease trajectory complementing IPF PROMs. Implementation of the PREM will enable commissioners and providers to improve the quality of the services and the patient experience of care delivered across the wider inter-disciplinary team. Reference: DH 2011 NHS Patient Experience Framework.